Bad Mothers and Strange Offspring: Images of Scrubfowl and Sea Turtles in Eastern Indonesia - Gregory Forth (Ethnobiology Letters, 2020)
One way birds communicate knowledge to humans and facilitate communication among humans is through metaphors. A recent book discusses animal metaphors, nearly a third of which employ birds as vehicles, used by the Nage people of Flores Island (eastern Indonesia). As applied to human beings and human behaviors, bird metaphors reveal considerable overlap with other animal metaphors; thus, a full understanding of these requires additional attention to the metaphoric or more generally symbolic value of other sorts of non-human animals. Emphasizing how knowledge of birds is shaped in some degree by an extra-cultural empirical experience of the creatures, the present discussion explores similar representations of a bird, the scrubfowl, and a marine reptile, the sea turtle, among people in several parts of Flores.